1998
DOI: 10.2172/645467
|View full text |Cite
|
Sign up to set email alerts
|

The development and use of radionuclide generators in nuclear medicine -- recent advances and future perspectives

Abstract: This is a preprint of a paper intended for presentation at a scientific meeeting. Because of the provisional nature of its content and since changes of substance or detail may have 10 be made before publication, the preprint is made available on the understanding that it will not be cited in the literature or in any way be reproduced in its present form. The view expressed and the Statements made remain the responsibility of the named author(s); the views do not necessarily reflect those of the government of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…So, the radioisotope concentrator device should be developed to increase the concentration and quality of injectable 99m Tc eluates and consequently the generator life time or the effectiveness of the generator utilisation. Some concentration methods have been developed for increasing 99m Tc concentration of the saline eluate for extension of the life time of the fission- 99 Mo-based 99m Tc generators [38][39][40][41][42][43][44]. All these methods used a chloride-removing column containing Ag+ ions, which couple with a pertechnetate-concentrating sorbent column such as alumina, Bonelut-SAX, QMA, and multifunctional sorbent.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…So, the radioisotope concentrator device should be developed to increase the concentration and quality of injectable 99m Tc eluates and consequently the generator life time or the effectiveness of the generator utilisation. Some concentration methods have been developed for increasing 99m Tc concentration of the saline eluate for extension of the life time of the fission- 99 Mo-based 99m Tc generators [38][39][40][41][42][43][44]. All these methods used a chloride-removing column containing Ag+ ions, which couple with a pertechnetate-concentrating sorbent column such as alumina, Bonelut-SAX, QMA, and multifunctional sorbent.…”
Section: mentioning
confidence: 99%
“…Several research groups reported on using different nonsaline aqueous eluents for elution of 99m Tc from alumina-based generator systems which couple with a concentration unit for increasing the pertechnetate concentration of the 99m Tc solution. The eluents used are the following: the mixture of 0.7 M acetic acid and 0.0225 M NaCl solution [50], the solution of the salt of weak acids such as ammonium acetate, citrate, titrate, and so forth, and the mixture of acetic acid and ammonium acetate solution [43][44][45][46][47][48]. Although the elution performance of these eluents is excellent and suitable for the concentration processes using an anion exchange materials such as QMA Sep-Pak Cartridge, NH 2 Amberlite, BondElut SAX, Dowex-1, DEAE Cellulose, and so forth, the large volume of the eluents used for the 99m Tc elution from large alumina column-based generators is the main issue for the routine use of all these methods.…”
Section: (I) Nonsaline Aqueous Solution-eluted 99mentioning
confidence: 99%
“…TABELA 3 -Isótopos radioativos de rênio [52] . [58,59] . FIGURA 8 -Esquema detalhado de funcionamento do sistema de concentração com trocadores catiônico/aniônico em série eluído com acetato de amônio 0,3 mol.L -1 [58,59] .…”
Section: Coluna De Gerador De Gelunclassified
“…Boyd [25] , em 1997, citou uma técnica de concentração para o gerador de FIGURA 13 -Esquema detalhado de funcionamento do sistema de concentração com trocadores catiônico/aniônico em série eluído com solução de NaCl 0,9 % [58,59] . FIGURA 14 -Gerador com coluna de alumina ácida "jumbo" (40 g, 20x90 mm) acoplada a um sistema de concentração com coluna aniônica DEAE celulose [17] .…”
Section: Reunclassified
See 1 more Smart Citation